Evidence of recent jungle yellow-fever activity in eastern Panama - Galindo, Pedro (1967)
Outbreaks of jungle yellow fever in man have been recorded twice from eastern Panama of recent years, first in 1948 and again in 1956. Since then, a close surveillance has been maintained on virus activity in eastern Panama. Recent field observations and serological tests on 402 monkey sera indicate that there was an outbreak of yellow fever among monkeys of southern Darién Province some time between 1963 and 1965. It does not appear that the outbreak has spread as yet to other areas. Virus transmission may have been permanently disrupted during the drought which affected the region in 1965. However, if the virus had managed to survive this unfavourable period, an epizootic wave might have evolved, invading forested areas immediately east of the Panama Canal, now inhabited by a dense non-immune human population.